Dreamweaver CS3 bible - Lowery, Joseph (Joseph W.) (Wiley ; John Wiley [distributor], 2007)
"Learn to create dynamic, data-driven Web sites using the exciting enhancements in the Dreamweaver CS3 version. You get a thorough understanding of the basics and then progress to learning how to produce pages with pizzazz, connect to live databases, integrate with Flash and Photoshop, use advanced technologies like Spry and Ajax, incorporate Flash, Shockwave, QuickTime, and WAV files, import Photoshop files directly into Dreamweaver, and enjoy Web success"--Resource description page